Poor management in protected areas is associated with lowered tropical mammal diversity. (20th July 2019) - Oberosler, V.; Tenan, S.; Zipkin, E. F.; Rovero, F.
Abstract: Numerous protected areas (PAs) have been created worldwide to safeguard wildlife and other natural resources from anthropogenic threats such as habitat destruction and bushmeat hunting. However, conservation efforts in many tropical PAs are still inadequate, revealing deficiencies in management effectiveness. It is therefore important to quantify how different protection regimes impact wildlife within PAs. We investigated the differences between forest mammal communities in two ecologically comparable PAs in the Udzungwa Mountains (Tanzania) with contrasting management regimes. One is a well‐protected national park with efficient law enforcement; the other has suffered decades of inadequate protection, mainly resulting in high levels of illegal hunting. Using camera‐trapping data, we assessed the target communities in terms of species richness, functional composition (i.e. proportions of trophic guilds) and species‐specific occurrences, all while accounting for imperfect detection. We found striking differences between the two mammal communities: lower species richness, alteration in the trophic structure and reduced occurrence probabilities for most species in the forest with high disturbance. The difference in occurrence probability between the two PAs tended to be highest for larger‐bodied species. Our results show that strictly enforced legal protection is required to maintain diverse mammal communities in tropical forests under ever‐increasing anthropogenic threats. While PAs are the cornerstone of efforts to conserve tropical biodiversity, the future of biodiversity within them is closely tied to the effectiveness of enforcement. Abstract : As conservation efforts in many tropical protected areas remain inadequate it is important to quantify how different protection regimes impact wildlife within PAs. Using camera trapping data, we investigated the differences between forest mammal communities in two ecologically comparable PAs in Tanzania with contrasting management regimes, specifically in terms of species richness, functional composition and species‐specific occurrences. We found striking differences between the two mammal communities, with lower species richness, alteration in the trophic structure, and reduced species occurrence probabilities in the forest with high disturbance. Our results show that strictly‐enforced legal protection is required to maintain diverse mammal communities in tropical forests under ever‐increasing anthropogenic threats.